Comparison of fatty acid content in Camellia oleifera (L.) Kuntze oil and olive oil by GC (Bangladesh Journal of Botany, 2015)
The comparison of fatty acid content in Camellia oleifera (L.) Kuntze oil and olive oil was done by GC. C. oleifera oil contained more C18:1n9c, C18:2n6c, C20:1 and C22:1n9 than olive oil. Olive oil did not contain C21:0 and C24:1 but more C8:0, C16:0, C16:1, C18:0, C18:3n6, C18:3n3, C20:2, C22:0, C23:0 and C24:0 than C. oleifera oil, C. oleifera oil did not contain C20:2. C. oleifera oil and olive oil are beneficial for human health for their unsaturated fatty acids content and C. oleifera oil is healthy than olive oil. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22741 Bangladesh J. Bot. 44(1): 155-157, 2015 (March)